El encuentro entre filosofía y revelación en el De principiis de Orígenes (2013)
The article tries to understand how the interaction between Philosophy and Christianity is given in an emblematic work, for this topic, as Origen’s De principiis. After contextualizing the problem, the article studies some programmatic statements of the prologue and then some paradigmatic doctrinal cases: the immateriality of God, the created the character of matter and incarnation. Then, teh text concludes with a balance.